Port of Spain, Trinidad, Brunswick Square - (:unkn) unknown (My University, 2010)
A view of tree lined path in Brunswick Square located in Port of Spain in the early 20th century. Today the Square is called Woodford Square, so named after Governor Sir Ralph Woodford who ruled Trinidad in the 1850s.The postcard is addressed to Mr. Herbert Hampton, Massachuetts, United States.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Plazas--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; 1902; Trees--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago; Brunswick Square (Port of Spain); Woodford Square (Port of Spain)